2021
DOI: 10.7150/ijms.51297
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 5 correlated with immune infiltration serves as a prognostic biomarker in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is the predominant subtype of lung cancer with a relatively poor prognosis. The dramatic improvements of new immunotherapy strategies have shown promising results in lung cancer patients. This study aimed to elucidate the functions of immune-associated genes in LUAD prognosis and pathogenesis by analyzing public databases. We obtained expression profiles of LUAD patients from The Cancer Genome Atlas (TCGA) database and applied the ESTIMATE algorithm to calculate immune scores and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The tumor microenvironment (TME) is a complex network that comprises various cell types, cytokines and other extracellular components and plays a fundamental role in cancer recognition and treatment [ 18 ]. Over the past decade, immunotherapy targeting specific tumor-infiltrating immune cells (TIICs) and immune checkpoint inhibitors (ICIS) has been proven to improve the therapy response and clinical outcome of patients with LUAD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is a complex network that comprises various cell types, cytokines and other extracellular components and plays a fundamental role in cancer recognition and treatment [ 18 ]. Over the past decade, immunotherapy targeting specific tumor-infiltrating immune cells (TIICs) and immune checkpoint inhibitors (ICIS) has been proven to improve the therapy response and clinical outcome of patients with LUAD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…HSF5 is not a well-known factor among the HSF family members. However, in lung adenocarcinoma, it has been shown that HSF5 plays a regulatory role in immune infiltration, suggesting that this isoform may serve as a potential immunotherapy target 28 . HSFX and HSFY are located on the X chromosome and Y chromosome, respectively.…”
Section: Hsf1 Family Proteins and Their Structuresmentioning
confidence: 99%
“…In addition to its role in spermatogenesis [ 24 , 25 , 26 ], HSF5 was found to be downregulated in lung adenocarcinoma patients within the Cancer Genome Atlas (TCGA) cohort. Its expression was also found to positively correlate with patients’ overall survival, inflammatory responses, and immune cell infiltration [ 27 ]. In contrast, HSFY has been reported to be involved in germ cell development, whereby the deletion of HSFY results in male infertility [ 28 , 29 ].…”
Section: Overview Of the Heat Shock Response (Hsr)mentioning
confidence: 99%